Clinico-radiological variability of pulmonary tuberculosis in young patients as compared to elder patients prior to RNTCP and after 18 years RNTCP - Joshi, Jawahar L.; Devi, Sunita; Mohan, Vinay; Kaur, Ritu P.; Kaur, Ramandeep (International Journal of Research in Medical Sciences, 2018)
Background: Tuberculosis, a chronic disease causing high morbidity and mortality with multiple host related and socio-demographic risk factors. Incidence is 3-4 times among in diabetics. HIV is considered to be a most powerful risk factor other being malnutrition, Tubercular contacts, smoking habits and alcoholism. Many ecological and societal threats increase a vulnerability to infection and succession of the disease. Objective was to study and compare various clinico-radiological presentations and clinical risk factors for pulmonary tuberculosis in the young (<50yrs) and elderly (>50yrs) patients. Methods: Total 300 pulmonary tuberculosis patients each admitted in hospital during 1999 (group ‘A’) and 2016 (group ‘B’) respectively were included in our study. Socio-demographic risk factors and presence of any existing co morbidities and clinical as well radiological presentation data were evaluated. Results: Majority patients in both group ‘A’ and ‘B’ were males (67% and 61.3%), younger (71.3% and 63.3%) patients. Elder patients had more smokers in both groups (48.8% and 33.6%). COPD trends seems to be receding in group ‘B’ as compared to group ‘A’ in younger (6.3% vs. 8.9%) as well elder (13.6% vs. 29.1%) but on the contrary lifestyle disease trends like DM increased in group ‘B’ than group ‘A’ patients more in elder subgroup (30% vs. 9.3%). HIV infected was more in younger 2.1 % (elder 0.9%) group ‘B’ patients. Haemoptysis (17.8% and 18.6% vs. 13.7% and 9.1%) and cough (~87% vs. ~85%) were almost similar but fever (~90% vs. ~65%) was seen significantly higher in the young patients. Radiologically bilateral upper lobe cavitations (15%-30%) was a higher in group A patients as compared to negligible less than ~3% cavitations in group B, on the contrary infiltrations (15%-32%) was more in group B. Conclusions: Young adults are more likely to have fever while haemoptysis cough and advanced lung field involvement is more common in elderly. Elderly patients had a higher number of co-morbidities like COPD and DM. The present study reveals that various demographic, socioeconomic and clinical risk factors have a potential role in causation/augmentation of pulmonary tuberculosis hence life style modification, prevention and timely management of these risk factors could be helpful to reduce the burden of disease.